2015
DOI: 10.1093/jee/tov030
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Essential Oil of Zingiber purpureum Rhizomes and Its Main Compounds against Two Stored Product Insects

Abstract: The insecticidal and repellent activities of the essential oil extracted from Zingiber purpureum Roscoe rhizomes were evaluated against Tribolium castaneum (Herbst) and Lasioderma serricorne (L.) adults. During our screening program for agrochemicals from Chinese medicinal herbs and wild plants, the essential oil of Z. purpureum rhizomes was found to possess strong contact toxicity against T. castaneum and L. serricorne adults, with LD50 values of 39.0 and 16.3 µg per adult, respectively, and also showed stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 20 publications
3
24
0
2
Order By: Relevance
“…The essential oil of A. anethoides exhibited obvious repellent activity against T. castaneum and L. serricorne 22,23) and be got at the same laboratory with author. 22,23) and be got at the same laboratory with author.…”
Section: Repellent Activitymentioning
confidence: 99%
“…The essential oil of A. anethoides exhibited obvious repellent activity against T. castaneum and L. serricorne 22,23) and be got at the same laboratory with author. 22,23) and be got at the same laboratory with author.…”
Section: Repellent Activitymentioning
confidence: 99%
“…EOs obtained from lemon and eucalyptus are used as the active substances in non-toxic repellent products that are recommended for children. Moreover, several studies demonstrate that EOs do not only repel the insects but also act on them as neurotoxic compounds [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, linalool exhibited contact toxicity with an LC 50 of 105.63 µg/cm 2 against S. oryzae and Tribolium castaneum [27]. Wang et al found that the essential oil from Z. purpureum rhizomes possessed strong contact toxicity against T. castaneum and Lasioderma serricorne adults, with LD 50 values of 39.0 and 16.3 µg per adult, respectively [28]. However, the contact toxicity of tea saponins has rarely been reported [29].…”
Section: Discussionmentioning
confidence: 99%